2010
DOI: 10.1016/j.toxicon.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Can LASSBio 596 and dexamethasone treat acute lung and liver inflammation induced by microcystin-LR?

Abstract: The treatment of microcystin-LR (MCYST-LR)-induced lung inflammation has never been reported. Hence, LASSBio 596, an anti-inflammatory drug candidate, designed as symbiotic agent that modulates TNF-alpha levels and inhibits phosphodiesterase types 4 and 5, or dexamethasone were tested in this condition. Swiss mice were intraperitoneally (i.p.) injected with 60 microl of saline (CTRL) or a sub-lethal dose of MCYST-LR (40 micrg/kg). 6 h later they were treated (i.p.) with saline (TOX), LASSBio 596 (10 mg/kg, L59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…This inhibition results in hyperphosphorylation of cytoskeleton proteins, consequently discontinuing some cellular processes like arrangement of the cytoskeleton subunits and cellecell adhesion (Frangez et al, 2003). Nevertheless, another parallel mechanism has been already demonstrated, which also explains MC-LR toxicity: the redox system imbalance that can end up in inflammation (Nobre et al, 2003;Carvalho et al, 2010;Mattos et al, 2014). Indeed, the toxin intranasally administered to our mice could eventually reach the lung and trigger the inflammatory response observed.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This inhibition results in hyperphosphorylation of cytoskeleton proteins, consequently discontinuing some cellular processes like arrangement of the cytoskeleton subunits and cellecell adhesion (Frangez et al, 2003). Nevertheless, another parallel mechanism has been already demonstrated, which also explains MC-LR toxicity: the redox system imbalance that can end up in inflammation (Nobre et al, 2003;Carvalho et al, 2010;Mattos et al, 2014). Indeed, the toxin intranasally administered to our mice could eventually reach the lung and trigger the inflammatory response observed.…”
Section: Discussionmentioning
confidence: 65%
“…injection of MC-LR (Picanço et al, 2004;Soares et al, 2007;Carvalho et al, 2010;Casquilho et al, 2011). However, the functional and histological assessments following a sub-chronic exposure to low doses are still poorly documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LASSBio-596 was reported to effectively prevent mechanical and morphometric changes in the lung, and it was observed to block fibroproliferation in a BALB/c mouse model of asthma [12]. It was also reported that LASSBio-596 prevented lung and hepatic inflammation and completely blocked pulmonary functional and morphological changes induced by microcystins [25,26]. Because of this important anti-inflammatory action, we begin the study of LASSBio-596 in inflammatory angiogenesis, believing in its potential antiangiogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all these therapies reduced liver dysfunction. Similarly, in experimental lung injury induced by endotoxin [17] and microcystin-LR [18,19], i.p. administration of LASSBio596 has been shown to reduce pulmonary functional impairment and TNF-α.…”
Section: Kidney and Liver Functionmentioning
confidence: 93%
“…Our group reported the use of LASSBio596 to treat ARDS induced by E.coli lipopolysaccharide [17]. This compound effectively reduced pulmonary inflammation in experimental lung injury induced by endotoxin [17] and microcystin-LR [18,19], and elastase induced emphysema [20].…”
Section: Introductionmentioning
confidence: 99%